1961
DOI: 10.1002/pol.1961.1205516238
|View full text |Cite
|
Sign up to set email alerts
|

The homopolymerization of maleic anhydride

Abstract: S31tween Flory's and Hermans' equations cannot be made a t this time as a result of this work. The wide rurrent discussions on the theory of network ~t r u c t u r e s~-~ indicate that a rigorous analysis of this very complex problem must await further experimental data on numerous other polymer systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1964
1964
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Because unsaturated dibasic acids like maleic acid do not polymerize alone, 18 the grafting of dibasic acid onto ref-1 was carried out in the presence of an initiator (peroxodisulfate) and a small quantity of vinyl acetate at 60°C (+ 1°C). It was observed that when initial dibasic acid concentrations of 1% were used, grafting onto ref-1 ceased after 2 h, as determined acidometrically.…”
Section: Resultsmentioning
confidence: 99%
“…Because unsaturated dibasic acids like maleic acid do not polymerize alone, 18 the grafting of dibasic acid onto ref-1 was carried out in the presence of an initiator (peroxodisulfate) and a small quantity of vinyl acetate at 60°C (+ 1°C). It was observed that when initial dibasic acid concentrations of 1% were used, grafting onto ref-1 ceased after 2 h, as determined acidometrically.…”
Section: Resultsmentioning
confidence: 99%
“…The homopolymerization processes of MA induced by UV irradiation, sometimes in dehyde, benzoic acid, and ethylbenzoate, mainly derived from the primary photofragmentation of the presence of suitable sensitizers. [49][50][51][52] 3. The light-induced copolymerization prothe BEE photoinitiator, followed by further addition or oxidation modification reactions.…”
Section: Light-induced Grafting Reactions Of Maleicmentioning
confidence: 99%
“…The solvent, electrolyte and the reference electrode were the same as those used in cyclic voltammetry. Platinum foils (1 in.') were used as working and counter electrodes.…”
Section: Polymerization Proceduresmentioning
confidence: 99%